Kemas Ulang Informasi dalam Pembuatan Buku Pintar Siaga (Studi Kasus: Pada Kantor Badan Penanggulangan Bencana Daerah Sumatera Barat) - Frantika, Rezky; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractDisaster is an event or series of events that threatens and disrupts people's lives and livelihoods caused by natural factors and non-natural factors and human factors resulting in human casualties, environmental damage, property losses, and psychological impacts, a phenomenon of life humans who cannot be known exactly when it happened. In facing disaster preparedness in Indonesia, there is still a lack and lack of hate education so that there is a lack of public knowledge in post-disaster planning and their readiness to anticipate disasters. Therefore, repacking information is packing information back, or changing from one form of information, to a symbol that is interpreted as a message, recorded as a sign, or sent as a signal. Preparing knowledge about disaster preparedness or hate from an early age to people who are vulnerable to disasters and in preparing themselves for disasters.Keywords: information, repackaging, disaster